2022
DOI: 10.25165/j.ijabe.20221504.5406
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional requirements and precise fertilization of wine grapes in the eastern foothills of Helan Mountain

Abstract: Cabernet Sauvignon grapes in the wine-producing area of Helan Mountain, East Ningxia, China, were the research object in this study. The dissection of the roots and branching stems method was used to explore the dynamic changes in the nitrogen, phosphorus, and potassium nutrient requirements of wine grapes over a number of growth stages. The results showed that over the whole growth period, the nitrogen content of the roots was the highest during the leaf-expansion stage and lowest during the turning-color sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Changes in lighting conditions have a significant impact on nutrient prediction results, which has been validated by experimental results. It had high accuracy in leaf detection [3,4], but low accuracy in canopy detection [1,2]. Preprocessing algorithms were mainly aimed at removing the background and correcting colors, without addressing color differences caused by lighting changes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in lighting conditions have a significant impact on nutrient prediction results, which has been validated by experimental results. It had high accuracy in leaf detection [3,4], but low accuracy in canopy detection [1,2]. Preprocessing algorithms were mainly aimed at removing the background and correcting colors, without addressing color differences caused by lighting changes.…”
Section: Discussionmentioning
confidence: 99%
“…Jiang et al studied the dynamic changes in the N, P, and K requirements of wine grapes over different growth stages using the dissection of roots and the branching stems method. The optimal nutrient levels of the trees at different stages were obtained [3]. Sun et al used the diagnosis-and recommendation-integrated system to obtain the best nitrogen status of apple leaf [9].…”
Section: Techniques For Generating Leaf Suitable Nutrient Standardsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the intrinsic relationship between soil nutrients, they are bound to have an impact on grapevine and grape quality. Many previous studies have shown that different vineyard soil nutrients are different [7,8], and that different soil nutrients have different effects on grape plant growth and grape quality [9][10][11].…”
Section: Introductionmentioning
confidence: 99%